Large-sized liquid capsule and method for manufacturing the same

The method of solidifying a core material and hardener mixture, then coating it with a film-forming agent, addresses the limitations of small encapsulated food sizes by enabling the production of larger, stronger capsules with improved structural integrity and sensory appeal.

JP2025066600APending Publication Date: 2025-04-23TOTTORI INST OF IND TECH

Patent Information

Application Number
JP2023176322
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-23

AI Technical Summary

Technical Problem

Existing methods for producing encapsulated foods using liquid core materials are limited to small sizes due to manufacturing constraints, and large capsules are inefficient to produce and prone to seam-related issues.

Method used

A method involving the solidification of a core material and hardener mixture, followed by immersion in a contact solution containing a film-forming agent like sodium alginate, to form a coating and create larger capsules with improved structural integrity.

Benefits of technology

This method allows for the production of larger capsules with enhanced strength and elasticity, capable of containing significant volumes of liquid core material while maintaining structural integrity and sensory appeal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066600000001_ABST
    Figure 2025066600000001_ABST
Patent Text Reader

Abstract

To provide a capsule containing a content.SOLUTION: There are provided a method for manufacturing a capsule including: a step of solidifying a content containing a core substance and a curing agent to generate a solidified content; a step of bringing the solidified content in contact with a solution containing a coating film forming agent; a step of separating the solidified content from the solution after a prescribed time from the contact; and a step of cleaning the surface of the separated solidified content, and a capsule containing the content. This makes it possible to provide a capsule food product in which the coating film surrounds the core substance. The core substance may contain high concentration alcohol. The curing agent may contain calcium ion, iron ion, aluminum ion or the like, or a salt thereof. Contact with the solution may be performed by immersing the solidified content into the solution.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a capsule containing a liquid, and in particular to an encapsulated food, medicine or other product. [Background technology]

[0002] Unlike solids, liquids cannot maintain their shape, and it is difficult to move liquids alone without placing them in a container. Liquids are prone to interact with taste, olfactory, and tactile organs and various sensors when they come into contact with them. For this reason, capsules such as capsule foods and capsules made of materials that are less likely to interact with the sensory organs when they come into contact with the food are useful. For example, food capsules that maintain their shape until they are put into the mouth and do not interact with the sensory organs are widely used. In the manufacture of food capsules, for example, the liquid-hardening coating method (orifice method) is used to manufacture artificial salmon roe. In this method, the liquid (core material) to be encapsulated in the capsule is dispersed in a polymer liquid such as alginic acid, and is dropped into a hardening liquid containing calcium. Then, a spherical gel can be made by rolling it up due to surface tension. In such soft capsules, ingredients of medicines, health foods, foods, animal feed, etc. are encapsulated in a coating prepared using a solution of proteins such as gelatin, polysaccharides such as starch, etc. Therefore, it is widely used in the food and pharmaceutical industries, etc.

[0003] While soft capsules are widely used as so-called health foods such as supplements, general foods using soft capsules are not well known. For example, a sour seasoning containing a soft capsule containing sesame aroma components and formed of a coating based on agar and gellan gum and / or carrageenan has been disclosed (e.g., Patent Document 1). In addition, a soft capsule for preventing deterioration of the texture of food, which is used in an edible medium containing edible oil, and contains agar as the main component of the coating, has been disclosed (e.g., Patent Document 2). These soft capsules have a small particle size of 3 mm or less.

[0004] Such encapsulation may be performed by the orifice method described above or the reverse orifice method (reverse method). The orifice method is a method in which a substance to be encapsulated (core substance) is mixed with a polymer, and the core substance mixed with a polymer is dropped into a hardening liquid that reacts with the polymer to cause gelation. For example, a method is disclosed in which a soy sauce solution containing a calcium salt and a soy sauce liquid is dropped into an aqueous sodium alginate solution to form a capsule (e.g., Patent Document 3). Also, a reverse spheronization process is disclosed in which wine such as sparkling wine is encapsulated (e.g., Patent Document 4). However, all of these food capsules are small. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-14252 A [Patent Document 2] JP 2018-143101 A [Patent Document 3] JP 2022-114451 A [Patent Document 4] International Publication No. WO2011 / 138478 Summary of the Invention [Problem to be solved by the invention]

[0006] Capsules containing liquid produced by dripping are limited to such small sizes due to their manufacturing method. For example, food capsules such as artificial salmon roe can add new flavors and textures to the main food served at the same time, but the amount is small, making it difficult to enjoy the food capsule as it is. On the other hand, large food capsules are manufactured by manufacturing so-called empty capsules and filling them with food. However, this requires a capsule manufacturing process and a food filling process, which is not efficient. In addition, after filling, the filling opening needs to be sealed, and a seam-like thing is likely to remain. In general, seams tend to cause non-uniformity in strength, structure, or shape, and are likely to cause discomfort to the sensory organs. [Means for solving the problem]

[0007] In the orifice method or the reverse orifice method (reverse method), a capsule membrane is formed on the surface of a core substance by dropping the core substance onto the surface, which results in high productivity. These methods use a relatively weak force, such as surface tension, to form capsules, making it difficult to produce large-sized capsules.

[0008] In general, Laplace's equation is known for the shape of the free contact surface between two phases. ΔP=σ×(1 / R1+1 / R2) Here, ΔP is the pressure difference across the interface, σ is the surface tension, and R1 and R2 are the radii of curvature of the curved surfaces. Here, the surface tension of water is 72.75×10 -3 (N / m), and assuming R1 = R2 = 2 mm, ΔP = 72.75 × 10 -3 ×(1 / 0.002+1 / 0.002)=72N / m 2= 72 Pa. As the radii of curvature R1 and R2 become larger, ΔP becomes smaller and smaller, so it is clear that it is difficult to maintain this shape (for example, a sphere) by surface tension alone. Also, considering the effect of gravity, the shape of a non-wetting droplet (contact angle = 180 degrees) 500 on a solid substrate 510 can be expressed as follows (for example, Toshihiro Tanaka, Feram. 2003, 8 (3), 161) (see FIG. 27). dx / dφ=R cosφ dz / dφ=-R·sinφ R=1 / q1 q1=q2+q3-q4 q2=ρg / σ×(hz) q3=2 / b q4=sinφ / x where φ is the angle between the vertical axis and the normal to the point (x,z) on the contour, h is the height of the droplet, b is the radius of curvature at the apex of the droplet, ρ is the density of the droplet, and g is the acceleration of gravity (9.8 m / s 2 ) The density of water is approximately 1000 kg / m 3 and the surface tension is 72.75 mN / m. For example, if the height is h=3 mm and an appropriate b is selected, a flattened droplet shape with a width of about 30 mm can be obtained. It can also be seen that if the height exceeds h=5 mm, it becomes difficult to form droplets. If the surface tension is greater, larger droplets can be formed, but the droplets that can be formed with the surface tension of water are limited to this size. The volume of the droplet in this case is thought to be about 3 mL.

[0009] In addition, in food capsules encapsulated by the orifice method, the core material mixed with the polymer is dropped into the hardening liquid that reacts with the polymer to cause gelation, so there is a limit to the size of the droplets that are dropped. In relation to the nozzle diameter, etc., the following formula is considered to hold until the droplets are dropped (see Figure 28). ρg×4 / 3×πr2 3 ≦ 2πr1σ Here, ρ is the density of the liquid, σ is the surface tension of the liquid, and g is the gravitational acceleration. Here, the above radii r1 and r2 are close to the radius of the nozzle 520. If we approximately consider r1=r2=nozzle radius, for example, when the radius of the nozzle 520 exceeds 3.5 mm, the approximate weight becomes dominant and it becomes difficult to form the droplet 522. Incidentally, the volume of a sphere with a radius of 3.5 mm is approximately 0.18 mL. Therefore, it is difficult to drip large droplets using the orifice method.

[0010] In addition, the dropped droplets are flattened on the surface of the hardening liquid, then penetrate into the hardening liquid, and if the droplets have low wettability with the hardening liquid, they will form a shape close to a sphere to minimize the surface area due to surface tension, forming a coating of gelled polymer. Again, if the surface tension is low compared to the volume of the droplets, it will be difficult for them to form a sphere. Therefore, it is not easy to form large encapsulated foods.

[0011] For example, a dialysis membrane may be prepared in advance, shaped into a capsule, a mixture of a core substance and a polymer liquid may be enclosed within the membrane, and the mixture may then be dropped into a hardening liquid. However, this may cause the mixture to polymerize to the inside within a few hours, resulting in a jelly-like structure. Also, if a mixture of a core substance and a hardening liquid is enclosed within a membrane and dropped into a polymer liquid, as in the reverse orifice method, a capsule coating may form outside the membrane even if the membrane is coarse.

[0012] Therefore, a mixture of the core material and hardening liquid is poured into a mold corresponding to the shape of the capsule, frozen, and the frozen body is then poured into a polymer liquid to form a large capsule food.

[0013] More specifically, this may include the following: (1) A method for producing capsules, comprising the steps of solidifying a content containing a core material and a hardener to produce a solidified content, contacting the solidified content with a contacting solution containing a coating agent, separating the content coated by the contact from the contacting solution, and improving the coated content. The method may further include a step of washing the surface of the separated coated content. The capsules produced here may be used as a material to be processed in a process to impart other characteristics.

[0014] Here, the core material may be any of liquid, powder, and solid, or a combination thereof. For example, it may be any of alcohol, water, sugars such as glucose, sugar, fructose, etc., salt, and other water-soluble liquids or aqueous solutions, or a combination thereof. It may also include an alcoholic beverage that is a drink containing ethyl alcohol. For example, it may include any of sake, wine, whiskey, liqueur, vodka, etc., or a combination thereof. It may also include what are generally called fermented alcohol, distilled alcohol, and mixed alcohol, which are classified according to the production method. It may also include fats and oils and oil-soluble substances. Fat and oils may include, for example, coconut oil, vegetable oil, animal oil, and combinations thereof. Oil-soluble substances may include, for example, flavors, aroma oils, menthol, and combinations thereof. It may also include aqueous liquid foods such as soy sauce liquid, condensed milk, various vinegars, white soup stock, carbonated alcoholic beverages, lemon juice, fruit juice, coffee, and carbonated fruit drinks. In this way, it may include foods (including beverages) that are used as such.

[0015] The hardener may include a material that hardens (may include gelling) a material capable of forming a coating film described below. Specifically, the hardener may include a salt of a polyvalent cation. For example, Ca 2+ , Fe 2+ , Zn 2+ , Al 3+, or a combination of these ions. Calcium salts are preferred. Those used in food are preferred. For example, calcium lactate, calcium chloride, calcium gluconate, etc. may be included, or a combination of these may be included. Those with little bitterness are preferred. It is preferable not to include compounds with such unnecessary effects. Calcium lactate is preferred. When the core substance contains alcohol, it may be difficult for the hardening liquid containing the hardener to form a solution with the core substance. In general, calcium lactate has a solubility in water of 44 g / L (20°C) and 151 g / L (50°C), but it is said to be almost insoluble in alcohol. When mixed with water and ethyl alcohol, it is thought to dissolve according to the ratio. Dissolution of 2% or more is preferred. If it does not dissolve, a high-concentration calcium lactate aqueous solution can be prepared and dispersed in ethyl alcohol to increase the calcium lactate concentration. The contents include the core substance and the hardening agent, but may also contain other substances in a solid state, liquid state, gas state, or a combination of at least two of these. The hardening agent (e.g., calcium lactate) in the content is preferably 1% (weight) or more. It is preferably 1.5% (weight) or more, or 2% (weight) or more. The hardening agent (e.g., calcium lactate) in the content is preferably 5% (weight) or less. It is preferably 4% (weight) or less, or 3% (weight) or less. The viscosity of at least the liquid of the content may be 5 Pa·s or less, 1 Pa·s or less, 0.5 Pa·s or less, 0.1 Pa·s or less, 0.05 Pa·s or less, or 0.01 Pa·s or less. The lower the viscosity, the thinner the capsule is, and the easier it is to spread when broken. The viscosity of water is 1.002 mPa·s (0.001002 Pa·s) at 20°C, and the viscosity of ethanol is 1.200 mPa·s at 20°C, so in reality, the viscosity may be above this level.

[0016] Solidification may mean that a liquid substance has solidified or that a liquid substance has been hardened. For example, it may mean that a substance has become solid. It may also mean that the viscosity has reached a certain value or more. For example, it may mean that the viscosity has reached 0.1 Pa·s or more, 1 Pa·s or more, 5 Pa·s or more, or 10 Pa·s or more. It may also include a change in the state of a substance that involves a so-called phase change. For example, it may include the freezing of water or aqueous substances that contain water. Incidentally, the viscosity coefficient η of ice is 10 12 Pa·s, and temperature θ (℃) according to Weinberg μ θ =(12.44-4.02·θ+0.277·θ 2 ) x 10 11 Pa·s It is said that the liquid state and the solid state may be mixed. Here, for example, it may mean that the contents maintain their shape for a predetermined period of time when they come into contact with the contact solution. The predetermined period varies depending on the conditions under which the coating occurs, but may be a time or more that is sufficient for the coating to be performed. For example, it may be 30 seconds or more, 1 minute or more, or 3 minutes or more. On the other hand, if it is too long, productivity will also decrease, so it is realistic to use one hour or less. It is also possible to use a substance that undergoes solization and gelation depending on the temperature. Since the contents of a capsule are isolated by its coating, it is difficult to inject a solizing agent later. However, since heat can be transferred without the movement of substances, it is possible to use a gelled content during capsule formation (or coating formation) and sol the content after capsule formation (or coating formation). However, since capsule formation (or coating formation) utilizes a gelation reaction, it is preferable to use a solizing and gelling agent that does not inhibit this reaction. The solidified contents may refer to contents that have solidified and are capable of retaining their shape. The method for measuring viscosity is summarized in, for example, JIS Z8803, but a cone-disk type rotational viscometer may also be used. For example, the method may conform to JIS K 7117-2 (viscosity measurement method). For example, unless otherwise specified, the viscosity may be measured at a temperature of 23°C and a shear rate of 0.1 s -1However, if characteristics emerge under certain conditions (temperature, etc.), it is preferable to measure under those conditions.

[0017] The film-forming agent may mean one capable of forming a film that covers the solidified contents. It may include a gelling agent. It may include a compound or polymer capable of forming a soft capsule that may be used in food or medicine. For example, it may include a film-forming polymer. The film-forming polymer may include sodium alginate. The contact solution may include an aqueous solution. It may include an aqueous sodium alginate solution. If the concentration of the film-forming agent (including a compound or polymer (e.g., sodium alginate)) in the contact solution is too low, it becomes difficult to form a film. In general, about 0.5% (weight) is preferable. It is preferably 0.1% (weight) or more, 0.2% (weight) or more, or 0.3% (weight) or more. If the concentration of the film-forming agent (including a compound or polymer (e.g., sodium alginate)) in the contact solution is too high, it is not preferable because it reduces industrial productivity. In general, it is preferably 5% (weight) or less, 4% (weight) or less, or 3% (weight) or less. Contact may mean that the film-forming agent and the hardener are in close proximity to each other so that they can react with each other. Specific operations may include, for example, immersing and / or placing the contents in the contacting solution. It may include pouring or pouring the contacting solution onto the contents. It may include placing the contents in an environment sprayed with the contacting solution. Such contact may be performed for a predetermined time. The above-mentioned predetermined time may include a time sufficient for a coating to be formed on the surface of the solidified contents. This predetermined time may tend to be shorter when the concentration of the coating agent is higher and / or the temperature of the contacting solution is higher. Separating the contents from the contacting solution may include moving the contacting solution and / or the contents to a place where they are not in contact. Even if the contents are covered with a coating, there is a risk of unwanted reactions occurring within and / or on the surface of the coating. Washing the surface of the coated contents may include pouring or pouring a cleaning liquid onto the coated contents. Here, the frozen solidified contents come into contact with the contact solution at the surface, and at least a part of the contents is thawed from the surface, and the hardener and the film-forming agent contained therein react to form a film on the surface. It is believed that calcium ions, which are relatively mobile, contribute to this reaction.In the contacting step, a coating is formed on the surface of the contents that is capable of maintaining its shape / structure to some extent, and the contents (including a solidified state (which may include a highly viscous state) and a liquid state) may be separated from the environment (atmosphere).

[0018] In this way, the frozen hardening liquid containing a hardener and the contents containing a core substance are heated to a high temperature in a sodium alginate solution and rapidly thawed to form capsules. In order to improve the yield of capsule formation, it is preferable to optimize the conditions for forming the coating. This may include changing the temperature of the contact solution. In general, the higher the temperature, the higher the reaction rate, so a higher temperature may be used to improve the coating formation ability. In reality, a temperature equal to or lower than the boiling point of water is preferable. The step of improving the coated contents may be performed after the separation step, or during any of the steps described above, or before or after them. For example, the improvement step may include a step of adding a thickener to a mixture of the hardening liquid and the core substance to form the contents. In this way, the mixed contents may be solidified to generate a solidified contents. The contents may be returned from a solidified state to a liquid state while maintaining the shape of the capsule.

[0019] (2) The manufacturing method according to any one of the above, wherein the step of improving includes a step of increasing the concentration of the core substance in the contents. Here, the step of increasing the concentration of the core substance may be performed after the step of separating. For example, the step may include a step of immersing the capsule containing the separated coated contents in a liquid (which may include an aqueous solution or a solution) in which the concentration of the core substance is increased for a predetermined time. This predetermined time may include the time until the capsule obtains a desired core substance concentration. The predetermined time may be changed depending on temperature, concentration, and various other factors, but may be a time sufficient to obtain a desired concentration of the core substance in the capsule. For example, it may be 2 hours or more, 12 hours or more, or 18 hours or more. There is no particular upper limit, but a time until the capsule to be immersed does not deteriorate (below the deterioration time) is preferable. From an industrial point of view, 24 hours or less is preferable. In general, the higher the concentration and / or the higher the temperature, the shorter the predetermined time may tend to be. Here, the high concentration may mean a concentration equal to or greater than the core substance concentration of the contents of the capsule produced by the method of (1) above. The contents may include ethyl alcohol. The ethyl alcohol may include ethyl alcohol derived from tequila. The contents may include tequila. The contents may include at least one of the components contained in so-called alcoholic beverages.

[0020] (3) The manufacturing method according to any one of the above, wherein the step of improving includes a step of improving the coating. Here, the step of improving the coating may be performed after the step of separating. For example, the step of immersing the capsule containing the separated coated contents in a liquid (which may include an aqueous solution or solution) containing a component for improving (including modifying) the coating for a predetermined time may be included. The liquid containing a component for improving (including modifying) the coating may include a cationic solution. It may include one or more of poly-L-lysine, chitosan, and protamine. They may include an effective amount for improvement. For example, they may include 0.05 or 0.1% (by weight) or more. The liquid containing a component for improving (including modifying) the coating may include a solution containing a component that can be used as a coating agent. It may include at least one of gelatin, pectin, agar, sodium alginate, etc. They may include an effective amount for improvement. For example, they may include 0.05 or 0.1% (by weight) or more.

[0021] (4) The manufacturing method according to any one of the above, wherein the improving step includes a step of introducing a dye into the contents. Here, the step of introducing the dye may include a step of mixing a hardening liquid, a core material, and a dye to form the contents. In this way, the mixed contents may be solidified to generate a solidified contents. The contents may be returned from a solidified state to a liquid state while maintaining the shape of the capsule.

[0022] (5) The manufacturing method according to any one of the above, wherein the step of improving includes a step of introducing a water-soluble cellulose derivative into the contents. Here, the step of introducing the water-soluble cellulose derivative may include a step of mixing a hardening liquid, a core material, and a water-soluble cellulose derivative to form the contents. In this way, the mixed contents may be solidified to generate a solidified contents. The contents may be returned from a solidified state to a liquid state while maintaining the shape of the capsule. The water-soluble cellulose derivative may include various cellulose derivatives obtained by introducing different substituents to hydroxyl groups in cellulose molecules through ether bonds or ester bonds. For example, the water-soluble cellulose derivative may include those that are made water-soluble by breaking hydrogen bonds by chemically modifying the hydroxyl groups with ether group substitution or ester group substitution such as methyl groups. For example, methylcelluloses, hydroxypropylcelluloses, etc. may be included. It is considered that the capsules formed are less likely to be dented when a cellulose derivative (which may include, for example, methylcellulose) is added. If the concentration of the water-soluble cellulose derivative in the contents is too low, it becomes difficult to achieve sufficient function, and if it is too high, the characteristics may be deteriorated. For example, the concentration of the water-soluble cellulose derivative (e.g., methylcellulose) may generally be about 0.1% (by weight), preferably 0.01% (by weight) or more, 0.02% (by weight) or more, or 0.03% (by weight) or more, and preferably 2% (by weight) or less, 1% (by weight) or less, or 0.7% (by weight) or less.

[0023] (6) The manufacturing method according to any one of the above, wherein the step of improving includes a step of introducing a thickener into the contents. Here, the step of introducing a water-soluble cellulose derivative may include a step of mixing a hardening liquid, a core material, and a thickener to form the contents. In this way, the mixed contents may be solidified to generate a solidified contents. The contents may be returned from a solidified state to a liquid state while maintaining the shape of the capsule. The thickener may include, for example, gelatin, xanthan gum, guar gum, carrageenan, gum arabic, potato starch, etc. If the concentration of the thickener in the contents is too low, it may be difficult to thicken sufficiently, and if it is too high, there may be a risk of the properties being deteriorated. For example, the concentration of the thickener (e.g., xanthan gum) may generally be about 0.1% (by weight). It is preferably 0.01% (by weight) or more, 0.02% (by weight) or more, or 0.03% (by weight) or more. If it is too high, there is a risk that the desired state of the contents (e.g., liquid state) may not be obtained. 2% (by weight) or less, 1% (by weight) or less, or 0.7% (by weight) or less is preferred.

[0024] (7) Any of the above-described manufacturing methods, including a step of heating the contact solution to 40° C. or higher in the contacting step. Here, the step of heating to 40° C. or higher may include a step of heating the contact solution to 40° C. or higher in advance in the contacting step. The temperature of the contact solution is preferably 25° C. or higher, 40° C. or higher, or 60° C. or higher. At this temperature, a coating is formed, and therefore a temperature at which the reaction occurs sufficiently is preferable. The temperature is preferably lower than the temperature at which the contact solution boils in air. For example, it may be 80° C. or lower. Alternatively, it may be 60° C. to the temperature at which the contact solution boils. From the industrial viewpoint of the manufacturing process, it is preferably 70° C. or higher.

[0025] (8) The manufacturing method according to any one of the above, wherein the improving step includes a step of introducing a solid into the content. Here, the step of introducing a solid may include a step of mixing a hardening liquid, a core substance, and a solid to form a content. In this way, the mixed content may be solidified to produce a solidified content. The solid may include solids contained in fruit juice (e.g., fruit pulp, etc.) or other substances that enhance the palatability of the food.

[0026] (9) The manufacturing method according to any one of the above, wherein the step of improving includes a step of solidifying the solidified contents into a desired shape in the step of generating the solidified contents. Here, the step of solidifying into a desired shape may include a step of preparing a mold capable of obtaining the desired shape in the step of generating the solidified contents described above, and pouring the contents into the mold. In this manner, the step of generating the solidified contents by solidifying the contents may be performed. In this manner, the capsule having the desired shape may have the contents return from a solidified state to a liquid state while maintaining the shape.

[0027] As described above, any of the capsules described above can have the above-mentioned characteristics. The characteristics may include, for example, a higher concentration of the core material (close to the so-called concentrate). The characteristics may include a desired color. The characteristics may also include a characteristic taste, flavor, taste, etc. Characteristic may mean something different from other things or normal things. The characteristics may be the high concentration of the core material in the contents. The core material in the contents may be about 50% (volume), and the concentration of the core material in the contents is likely to be 50% or less of the original concentration. Therefore, there is a risk that the concentration of the core material is too low. For example, if the core material is tequila, the alcohol concentration is generally about 40% (volume). Even if tequila concentrate is used as the core material, the concentration is thought to be about 20% (volume) due to the addition of an equal amount of hardener. The characteristics may also be the texture of the capsule. The texture may include the chewing feel of the capsule. In other words, the chewing feel can be considered as the response of the capsule to compression deformation. If the capsule has elasticity, it may deform flat even if it is bitten hard, but may not break. On the other hand, if the capsule has elasticity but has low strength (i.e., the coating strength is low), the capsule may break (e.g., crush) and the contents may come out. On the other hand, if the capsule has no elasticity, the capsule may not deform much when bitten hard, but may break (e.g., crush) and the contents may come out. Furthermore, if the strength is weak, the capsule may break by itself when left to stand or may break when pinched with fingers. In order to reinforce the strength of the coating, the capsule may be immersed in a reinforcing coating solution containing a reinforcing component, and a reinforcing film may be added on the coating formed initially. This can increase the strength and add elasticity. The reinforcing coating solution may contain a poly-L-lysine solution. It may contain an agar solution. The poly-L-lysine solution (aqueous solution) may contain approximately 0.1% (by weight) of poly-L-lysine. Also, 0.01% (weight) or more, 0.02% (weight) or more, or 0.03% (weight) or more is preferred. 3% (weight) or less, 2% (weight) or less, or 1% (weight) or less is preferred. The agar solution (aqueous solution) may contain approximately 0.5% (weight) of agar. Also, 0.05% (weight) or more, 0.03% (weight) or more, or 0.05% (weight) or more is preferred. 5% (weight) or less, 4% (weight) or less, or 3% (weight) or less is preferred.

[0028] (10) A capsule comprising a core substance and a coating which contains the liquid content at 0°C or higher and a gel containing at least one of agar, carrageenan, gelatin, sodium alginate, calcium lactate, and pectin, the coating having an average thickness of 0.34 μm to 2 mm, the content being contained in a substantially spherical container formed by the coating, capable of being left stationary in the atmosphere, and maintained in a liquid state, the content being 6.3 ml or more.

[0029] Here, containing the contents may include substantially separating the contents including the core substance from the outside. The separation may include restricting the movement of the substance. It may also mean preventing at least a part of the core substance or contents from leaking out of the coating. The amount of the core substance may be 0.5 ml or more, 1 ml or more, or 3 ml or more. The amount of the contents including the core substance may be 0.5 ml or more, 1 ml or more, or 3 ml or more. There is no particular upper limit to the amount of the contents, but if it is too much, there is a high risk of self-destruction, and from an industrial perspective, it may be 1000 ml or less. The coating may have an average thickness of 10 μm (= 0.01 mm) or more, 20 μm (= 0.02 mm) or more, 30 μm (= 0.03 mm), 50 μm (= 0.05 mm) or more, or 100 μm (= 0.1 mm) or more. It is preferable that the thickness is such that substantial holes are formed in the coating due to the variation, and the core substance does not substantially leak out. If the coating is too thick, the industrial value may decrease, and the average thickness may be 10 mm or less, 5 mm or less, or 2 mm or less. The coating may be a semipermeable membrane. A semipermeable membrane may mean a membrane having the property that some substances can pass through while other substances cannot. In addition, such substances may be distinguished based on properties such as hydrophilicity and hydrophobicity (which may include lipophilicity), or based on the molecular weight of the molecules that constitute the substance, or these may be combined appropriately. Hydrophilicity is a property that is easily dissolved in water or easily mixed with water by forming hydrogen bonds with water, which may cause a thermodynamically favorable phenomenon (reducing free energy). In addition, hydrophobicity may be a property that has low affinity for water, is difficult to dissolve in water, or is difficult to mix with water. If it is not hydrophilic, it can be considered hydrophobic. A rough rule of thumb regarding the water solubility of organic compounds is that when there is at least one uncharged hydrophilic group per five carbons, or at least one charged hydrophilic group per seven carbons, the molecule will have a solubility in water of 1% or more by mass.Hydrophilic molecules (e.g., ethanol, etc.) or hydrophilic groups (e.g., carboxylic acid residues in fatty acids, etc.) can form hydrogen bonds due to their polarity, and therefore are more soluble in water than in oil or hydrophobic solvents. In polymers mainly composed of H, C, N, O, etc., if the molecular weight (particularly, there are number-average molecular weight and weight-average molecular weight, but here, weight-average molecular weight) is large, the size of the polymer generally becomes large. For example, considering semi-permeability (or selective permeability) based on ethanol, ethanol is hydrophilic, and the molecular weight of ethanol is 46, and it can permeate the coating (water itself can also permeate). Also, trypan blue is somewhat soluble in water and can be said to be hydrophilic, but its molecular weight is 961. Methyl red has a molecular weight of 269 and is almost insoluble in water, but water-soluble methyl red solutions and methyl red ethanol solutions are commercially available. Purple sweet potato pigment has a molecular weight of several hundred, is soluble in water, and can be said to be hydrophilic. Bromophenol blue has a molecular weight of 669 and is almost insoluble in water, but is soluble in ethanol. Lac dye has a molecular weight of about 2000, and its main component is laccaic acid obtained from lac scale insects. Water-soluble lac dyes and aqueous solutions are also available commercially. Among these dyes, trypan blue, methyl red, purple sweet potato dye, and bromophenol blue all permeated the coating, but lac dye did not. In other words, the semi-permeability here may be defined as a state in which molecules (or polymers) with a molecular weight of 1000 or less permeate, but molecules (or polymers) with a molecular weight of more than 1000 do not permeate. Here, 1000 is used as the standard, but it can also be distinguished using standards such as 500, 800, 1200, and 1500. The judgment of permeability / non-permeability does not necessarily have to be strict. It may be performed by checking the appearance of the dye with the naked eye, as in the above experimental example. In a system of a solute that does not permeate a semipermeable membrane and a solvent that shows permeability, when two solutions of different concentrations come into contact through the semipermeable membrane, osmotic pressure is generated at the separation, and only the solvent permeates. Substantially no leakage may mean that when placed in a windless atmosphere (e.g., 1 atmosphere and 25°C), the weight of the main body is 90% or more, 93% or more, or 96% or more of the original weight in one hour.Self-collapsing may mean that the coating breaks down due to internal pressure (such as pressure due to gravity) without the application of any other external force.

[0030] (11) Any of the capsules described above, wherein the content (core substance) is an aqueous solution containing 2% or more of ethyl alcohol. The percentage of ethyl alcohol contained in the core substance at a temperature of 15°C may be 2% or more, 4% or more, 15% or more, or 40% or more. For example, if the core substance is tequila, vodka, or whiskey, it is about 40%. If it is sake, it is about 15%, and if it is shochu, it is about 20 to 25%. If the content contains a core substance and a hardener (or hardener solution) and / or other components, the concentration of the characteristic component (e.g., ethyl alcohol) in the core substance in the content decreases.

[0031] (12) Any of the capsules described above, wherein the coating is a semipermeable membrane that is permeable to molecules having an average molecular weight of 1,000 or less. (13) Any of the capsules described above, wherein the contents include fruit juice. (14) Any of the capsules described above, wherein the contents contain a water-soluble cellulose derivative. (15) Any of the capsules described above, wherein the contents include a thickener. (16) Any of the capsules described above, wherein the coating seamlessly contains the contents. Seamless may mean that there is no seam or that the coating is performed in such a way that no seam is formed. In this case, when a membrane is formed in a sheet shape to contain the contents, the sheet has open ends, and these open ends are closed to completely contain the contents. At this time, at least two open ends are closed, so it is considered that seams are formed there. Such seams are likely to cause discontinuities in the properties and strength of the membrane. (17) Any of the capsules described above, wherein the contents include a solid material. The solid material may be visible through the coating, which can provide a visual impact. Effect of the Invention

[0032] In the examples of the present invention, a liquid core substance can be contained in an amount that is tangible enough to be felt as a beverage, whereas previously only a trace amount of the core substance could be contained. This makes it possible to provide a liquid food product that has an impact in terms of appearance, taste, and texture, and a method for producing the same. [Brief description of the drawings]

[0033] [Figure 1] 1 is a flowchart showing a method for manufacturing a capsule (material) in an embodiment of the present invention. [Diagram 2] 1 is a flowchart showing a method for manufacturing a high alcohol concentration capsule (material) in an embodiment of the present invention. [Diagram 3] 1 is a flowchart showing a method for manufacturing a highly elastic capsule (material) in an embodiment of the present invention. [Figure 4] 10 is a flowchart showing a method for producing a capsule (material) having other properties in an embodiment of the present invention. [Figure 5A] FIG. 2 is a diagram showing an example of a mold used when solidifying the contents in an embodiment of the present invention. [Figure 5B] FIG. 2 is a diagram showing an example of a mold used when solidifying the contents in an embodiment of the present invention. [Figure 5C] FIG. 2 is a diagram showing an example of a mold used when solidifying the contents in an embodiment of the present invention. [Figure 6] In the examples of the present invention, a photograph of a capsule (Experimental Example 1) is shown. [Figure 7] In the embodiment of the present invention, a photograph of a capsule (Experimental Example 2) is shown. [Figure 8] In the examples of the present invention, photographs of capsules (Experimental Examples 1 and 4) formed at various temperatures of sodium alginate solution are shown. [Figure 9] In the examples of the present invention, photographs of capsules (Experimental Examples 2 and 7) formed at various temperatures of sodium alginate solution are shown. [Figure 10]In the examples of the present invention, photographs of capsules (Experimental Examples 3 and 8) formed at various temperatures of sodium alginate solution are shown. [Figure 11] 1 is a graph showing the effect of the temperature of sodium alginate solution on the capsule formation rate in the examples of the present invention (Experimental Examples 1 and 4). [Figure 12] 1 is a graph showing the effect of the temperature of sodium alginate solution on the capsule formation rate in the examples of the present invention (Experimental Examples 2 and 7). [Figure 13] 1 is a graph showing the effect of the temperature of sodium alginate solution on the capsule formation rate in the examples of the present invention (Experimental Examples 3 and 8). [Figure 14] FIG. 13 is a graph showing the effect of Experimental Examples 5 and 6 on the breaking load. [Figure 15] FIG. 13 is a diagram showing the influence of Experimental Examples 5 and 6 on sample height. [Figure 16] FIG. 13 is a diagram showing the influence of Experimental Example 1, Experimental Example 6, and Experimental Example 9 on the sample height. [Figure 17A] FIG. 13 is a photograph of a capsule from Experimental Example 6. [Figure 17B] FIG. 13 is a photograph of a capsule from Experimental Example 10. [Figure 18A] FIG. 13 is a photograph of the capsule obtained in Experimental Example 12. [Figure 18B] FIG. 13 is a photograph of the capsule obtained in Experimental Example 13. [Figure 18C] FIG. 13 is a photograph of the capsule obtained in Experimental Example 14. [Figure 19] FIG. 13 is a photograph of the capsule of Experimental Example 15. [Figure 20] FIG. 1 is a diagram illustrating a method for measuring capsule strength. [Figure 21] FIG. 13 is a diagram showing capsule strength and sample height in Experimental Example 16. [Figure 22] FIG. 13 is a graph showing the effect on breaking load in Experimental Example 17. [Diagram 23] FIG. 13 is a diagram showing the effect on sample height in Experimental Example 17. [Figure 24]FIG. 13 is a graph showing the effect on breaking load in Experimental Example 17. [Diagram 25] FIG. 13 is a diagram showing the effect on sample height in Experimental Example 17. [Figure 26] 13 is a graph showing the change over time in the alcohol concentration of the capsule liquid in Experimental Example 18. [Figure 27] FIG. 1 is a diagram illustrating a model of a droplet. [Figure 28] FIG. 1 is a diagram illustrating a model of a droplet dripping from a nozzle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] Hereinafter, embodiments of the present invention will be described with reference to the drawings. However, the present invention is not limited to these. EXAMPLES

[0035] 1 to 4 show a flowchart showing the process of manufacturing a capsule in an embodiment of the present invention. FIG. 1 shows the manufacturing process from the preparation of the substances and materials that are the components of the contents to the capsule material. A basic core substance, a hardener (details will be described later), and an optional characteristic material are prepared (S12, S14, S16). Here, the characteristic material is added to give a finished food a characteristic, and may include liquids and / or solids. For example, it may include a thickener, a colorant, a fiber component, etc. Appropriate amounts of each are mixed, dissolved, and / or dispersed (S18) to form a unified content (S20). Next, the content is solidified (S22). Solidification may simply include a process of increasing the viscosity of the content to a predetermined value (e.g., 1 Pa·s) or more, or may include a change in state accompanying a phase change (e.g., solidification in which a liquid becomes solid, etc.). Here, as an example, it is shown that at least the matrix component of the liquid content is solidified or solidified (e.g., a phase change from water to ice, etc.). The liquid or liquid content is placed in a predetermined mold (e.g., a plastic cup, a spherical container, etc.), and then cooled to a low temperature by placing it in a freezer or the like, so that at least a part of the content is solidified. Here, the mold may be a mold that can be assembled and / or disassembled. If a solidified product of a desired shape cannot be obtained in one step, a process of making multiple parts and combining them (which may include refreezing) may be performed. Water starts to solidify at 0°C (freezing point) or lower at atmospheric pressure, but in the case of a mixture with water or alcohol, etc., it is cooled to a lower temperature. For example, the temperature may be below the freezing point of at least a part of the content, such as -20°C or lower, -40°C or lower, -50°C or lower, -60°C or lower, -70°C or lower, -80°C or lower, -90°C or lower, -100°C or lower, -110°C or lower, or -120°C or lower. The freezing point of ethyl alcohol is -117°C. On the other hand, it is difficult industrially to lower the temperature to below the boiling point of liquid nitrogen, which is -196°C. After solidification in this manner, the mold is disassembled or destroyed, the solidified contents are removed, and the process proceeds to the next step, in which the solidified contents are immersed in a contact solution (details of which will be described later) contained in a container and brought into contact with the solution (S24).At this time, the film-forming component (e.g., polymer component, etc.) contained in the contact solution reacts with the hardener (e.g., calcium compound, etc.) contained in the contents during contact to form a film on the surface of the contents. Since the entire solidified contents are immersed in the contact solution, a film is formed on the entire surface, making it difficult to form seams in particular. In order to promote this reaction, the contact solution may be heated in advance. After immersion for a predetermined time, the film-covered contents are removed from the contact container (S26). At this time, it is preferable that the solidified contents are warmed and at least a part of them is liquid or liquid-like. The capsule material is thus completed (S28). This material may be used as a finished product as a capsule as it is. In addition, if necessary, it can be added to such capsule material having high concentration alcohol (Fig. 2), high elasticity (Fig. 3), or other characteristics (Fig. 4) to give new value.

[0036] [Preparation of contents] As the core material, commercially available tequila (ethyl alcohol 40% (volume); product name: Tequila Silver; manufactured by Sauza (Mexico); imported by Suntory Holdings Limited) and commercially available orange juice (product name: POM Pon Juice; name: mixed fruit juice (concentrated and reduced); raw materials: fruit (orange (Brazil), Unshu mandarin orange (domestic)) / flavoring) were prepared. As the hardener, a 4% calcium lactate aqueous solution (reagent name: calcium lactate (powder); manufactured by Junsei Chemical Co., Ltd.) was prepared. Furthermore, as a thickener, commercially available xanthan gum (product name: xanthan gum standard (powder); manufactured by Unitech Foods Co., Ltd.) was prepared, and each was made into a 0.2% and 0.5% (weight) xanthan gum aqueous solution using deionized water. In addition, commercially available methylcellulose (product name: methylcellulose H (powder); manufactured by Unitech Foods Co., Ltd.) was prepared, and a 0.2% (weight) methylcellulose aqueous solution was prepared using deionized water. In addition, commercially available crystalline cellulose (product name: domestic fine powder crystalline cellulose, manufactured by Nippon Garlic Co., Ltd.) was prepared, and a 0.2% (weight) crystalline cellulose aqueous solution was prepared. In addition, commercially available HMPC cellulose (product name: HMPC low concentration type, manufactured by Unitech Foods Co., Ltd.) was prepared, and a 0.2% (weight) HMPC cellulose aqueous solution was prepared. In addition, purple sweet potato pigment (product name: KC Red SL-9 (aqueous liquid), manufactured by Kobe Chemical Industry Co., Ltd.), gardenia red pigment (product name: KC Red KL-7 (aqueous liquid), manufactured by Kobe Chemical Industry Co., Ltd.), and capsicum pigment (product name: KC Orange PE-EN (capsicum pigment emulsion preparation), manufactured by Kobe Chemical Industry Co., Ltd.) were prepared. In addition, commercially available lemon fruit (purchased at a supermarket) was prepared.

[0037] (Experimental Example 1) The contents were made by mixing equal amounts (volume) of tequila (basically 99% water and ethyl alcohol) with a 4% calcium lactate aqueous solution. Since the total volume is not expected to change even after mixing, the contents can be said to be basically an aqueous solution containing approximately 20% (volume) ethyl alcohol, approximately 2% (weight) calcium lactate, and water. (Experimental Example 2) The contents were made by mixing equal amounts (volume) of orange juice and 4% calcium lactate aqueous solution. Similarly, the contents can be said to be a mixture containing approximately 50% (volume) orange juice, approximately 2% (weight) calcium lactate, and water. (Experimental Example 3) The contents were prepared by mixing equal amounts (volumes) of deionized water and 4% calcium lactate aqueous solution. Therefore, it can be said that the contents consist of approximately 2% calcium lactate aqueous solution. (Experimental Example 4) The contents were prepared by mixing equal amounts (volume) of tequila and a mixed aqueous solution of 4% (weight) calcium lactate and 0.5% (weight) xanthan gum. Similarly, the contents were essentially composed of an aqueous solution containing approximately 20% (volume) ethyl alcohol, approximately 2% (weight) calcium lactate, approximately 0.25% (weight) xanthan gum, and water. (Experimental Example 5) The contents were prepared by mixing equal amounts (volume) of tequila and a mixed aqueous solution of 4% (weight) calcium lactate and 0.2% (weight) xanthan gum. Similarly, the contents were essentially composed of an aqueous solution containing approximately 20% (volume) ethyl alcohol, approximately 2% (weight) calcium lactate, approximately 0.1% (weight) xanthan gum, and water. (Experimental Example 6) The contents were prepared by mixing equal amounts (volume) of tequila and a mixed aqueous solution of 4% (weight) calcium lactate and 0.2% (weight) methylcellulose. Similarly, the contents were essentially composed of an aqueous solution containing approximately 20% (volume) ethyl alcohol, approximately 2% (weight) calcium lactate, approximately 0.1% (weight) methylcellulose, and water. (Experimental Example 7) The contents were prepared by mixing equal amounts (volume) of orange juice and a mixed aqueous solution of 4% calcium lactate and 0.5% xanthan gum. Similarly, the contents can be said to consist of a mixture containing approximately 50% (volume) orange juice, approximately 2% (weight) calcium lactate, approximately 0.25% xanthan gum, and water. (Experimental Example 8) The contents were prepared by mixing equal amounts (volume) of deionized water and a mixed aqueous solution of 4% calcium lactate and 0.5% xanthan gum. Therefore, the contents consisted of an aqueous solution containing approximately 2% (by weight) calcium lactate, approximately 0.25% (by weight) xanthan gum, and water. (Experimental Example 9) The contents were prepared by mixing equal amounts (volume) of tequila and a mixed aqueous solution of 4% (weight) calcium lactate and 0.2% (weight) crystalline cellulose. Therefore, the contents are essentially composed of an aqueous solution containing approximately 20% (volume) ethyl alcohol, approximately 2% (weight) calcium lactate, approximately 0.1% (weight) crystalline cellulose, and water. (Experimental Example 10) The contents were prepared by mixing equal amounts (volume) of tequila and a mixed aqueous solution of 4% (weight) calcium lactate and 0.2% (weight) HMPC cellulose. Therefore, it can be said that the contents are essentially composed of an aqueous solution containing approximately 20% (volume) ethyl alcohol, approximately 2% (weight) calcium lactate, approximately 0.1% (weight) HMPC cellulose, and water. HMPC cellulose, also known as hydroxypropyl methylcellulose, is a solid, off-white to beige powder that forms a colloid when dissolved in water (see chemical formula below). [ka] (Experimental Example 11) The contents were prepared by mixing equal amounts (volume) of orange juice and a mixed aqueous solution of 4% (weight) calcium lactate and 0.2% (weight) methylcellulose. Similarly, the contents can be said to be a mixture containing approximately 50% (volume) orange juice, approximately 2% (weight) calcium lactate, approximately 0.1% methylcellulose, and water.

[0038] [Freezing contents] (S22) In each of the above experimental examples, 7 ml of the contents (mixture) were placed in a hemispherical mold (100) and frozen (see FIG. 5A). The freezing temperature was −20 to −50° C. Furthermore, in order to form a perfect sphere, the frozen hemispherical contents were aligned with each other, and pressure was applied to ensure sufficient adhesion, and the freezing process was carried out again. As shown in FIG. 5A, the hemispherical contents 110 frozen in the hemispherical mold 100 may protrude slightly from the hemispherical mold 100 due to the expansion of water when frozen. When preparing a spherical frozen product, the contents 110 and another hemispherical contents 112 frozen in the same hemispherical mold are overlapped by processing the half-cut surfaces 116 of each other so that they fit, and a spherical frozen product 114 can be formed by refreezing. In addition, when making a capsule of a different shape, for example, a star-shaped mold 120 and a heart-shaped mold 130 as shown in FIG. 5B and FIG. 5C can be used.

[0039] [Preparation of contact solution] Commercially available sodium alginate (product name: sodium alginate (powder), manufactured by Marugo Corporation) was prepared, and a 0.5% (by weight) aqueous solution of sodium alginate was prepared using deionized water. [Contact with contact solution] (S24) About 50 ml of 0.5% sodium alginate aqueous solution was placed in a beaker and heated with a heater to prepare a contact solution consisting of a 0.5% sodium alginate aqueous solution at about 70°C. Experimental Examples 1 to 10 were then placed into this, one by one, to form a coating. At the same time, the solidified contents melted from the surface. Then, the contents were hardly mixed with the contact solution, and were separated from the contact solution by the formed coating. As a result, a capsule of about 3 cmΦ was formed. At this time, the temperature of the contact solution dropped by about 10°C.

[0040] [Separated from contact solution] (S26) The capsules formed, about 3 cm in diameter, were scooped up with a wire net and separated from the contact solution. After that, the wire net and the capsules were washed with running deionized water. Photographs of the capsules obtained in Experimental Example 1 and Experimental Example 2 are shown in Figures 6 and 7. By applying the reverse method in this way, stable capsule formation was achieved.

[0041] (Thickener and temperature) 8 to 10 show photographs of capsules when the temperatures of the contact solution are 4° C., 25° C., 40° C., 60° C., and 80° C. for Experimental Examples 1 to 4, 7, and 8. Also, Figs. 11 to 13 show graphs plotting the capsule yield against the temperature.

[0042] (Methylcellulose) In Experimental Examples 5 and 6, xanthan gum and methylcellulose were used as thickeners. The effects of these on the breaking load and sample height are shown in Figures 14 and 15. In addition, the influence of various celluloses on the sample height in Experimental Examples 6 and 9 is illustrated in Figure 16. In addition, it can be seen that since methylcellulose is used in Experimental Example 11, wrinkles do not form on the surface.

[0043] [Additional Contents 1] (Experimental Example 12) The contents were a mixture of equal amounts of tequila to which the above-mentioned purple sweet potato coloring had been added at 0.5% (volume) and a 4% aqueous solution of calcium lactate. (Experimental Example 13) The contents were a mixture of equal amounts of tequila to which the above-mentioned gardenia red pigment had been added at 0.5% (volume) and a 4% aqueous calcium lactate solution. (Experimental Example 14) The contents were a mixture of equal amounts of tequila to which the above-mentioned chili pepper coloring had been added at 0.5% (by weight) and a 4% aqueous calcium lactate solution.

[0044] Capsules were produced for each of these by carrying out the above-mentioned [freezing of contents], [contact with contact solution], [separation from contact solution], and washing. When these were stored in a preservation solution (the above-mentioned tequila (undiluted solution)), in (Experimental Example 12), the purple sweet potato pigment was a low molecular weight pigment, so the pigment leaked into the preservation solution. In (Experimental Example 13), the gardenia red pigment was a high molecular weight pigment, so the pigment did not leak into the preservation solution. In (Experimental Example 14), the capsicum pigment was a fat-soluble pigment, so the pigment did not leak into the preservation solution. By encapsulating appropriate pigments in this way, capsules with an impressive appearance were obtained. This state is shown in Figures 18A, 18B, and 18C.

[0045] [Additional Contents 2] (Experimental Example 15) The contents were made by mixing equal amounts of tequila and 4% calcium lactate aqueous solution, and then adding approximately 15% by weight of lemon fruit solids (pulp, etc.). The above-mentioned procedures for freezing the contents, contacting the contents with the contact solution, separating the contents from the contact solution, and washing were carried out to produce capsules. In this way, solid matter can be reliably enclosed in the capsules. This process is shown in Figure 19.

[0046] [Encapsulation coating reinforcement (coating treatment)] As shown in Fig. 3, a post-process can be carried out to reinforce the coating film produced in S24. For example, the capsule material obtained in the process of Fig. 1 is prepared (S62), and subjected to cationic solution treatment (S64) and coating solution treatment (S65). At this time, only the coating solution treatment (S65) may be carried out. The coating solution may contain a component that reinforces the coating film. After immersion for treatment, the food is separated from the solution (S66) and washed appropriately with deionized water or the like to obtain a highly elastic capsule (S68). (Experimental Example 16) A plurality of capsules of each type were prepared in the same manner as in Experimental Example 4, except that the amount of xanthan gum was 0%, 0.1%, and 0.25%. Half of each type were subjected to a coating treatment (S64) as shown in FIG. 3. The capsules were immersed in a cationic solution treatment liquid and allowed to stand at room temperature for about 10 minutes. The cationic solution treatment liquid at this time contained 0.1% poly-L-lysine (product name: Salad Keep, manufactured by Okuno Chemical Industries Co., Ltd.).

[0047] After that, the capsules that had been put in for immersion were scooped up with a wire net and separated from the cationic solution treatment liquid. Next, the capsules were put in a solution containing a coating agent for immersion and left to stand at room temperature for about 30 minutes. At this time, the solution containing the coating agent contained 0.5% (by weight) of agar (agarose) (product name: powdered agar that dissolves in hot water. Made by Ina Food Industry Co., Ltd.).

[0048] The capsules were then scooped out with a wire mesh, separated, and washed with deionized water. Chitosan is a type of polysaccharide, a copolymer consisting of randomly distributed β-1,4-linked D-glucosamine and N-acetyl-D-glucosamine. It is a cationic polymer of natural origin, and when dissolved in water, the hydrophilic groups (e.g., amino groups) become cationic, which is thought to easily attach to the capsule coating, which is thought to be anionic. This is thought to strengthen the capsule coating. [ka]

[0049] Protamine is the main component of protein extracted from fish testes (molecular weight approximately 4,600). Protamine has many amino or guanidyl groups and is positively charged up to slightly alkaline pH. It is therefore believed to adhere easily to the capsule coating, which is considered to be anionic. This is believed to strengthen the capsule coating. Polylysine (ε-poly-L-lysine, EPL) is a low molecular weight natural homopolymer of L-lysine, an essential amino acid, and is produced by bacterial fermentation. ε-polylysine contains hydrophilic amino groups and is positively charged in water. It is therefore believed to adhere easily to the capsule coating, which is considered to be anionic. This is believed to strengthen the capsule coating. In this experimental example, a cationic solution containing poly-L-lysine was used, but a cationic solution containing chitosan (e.g., a commercially available product under the trade name of Koyo Chitosan FL80, manufactured by Koyo Chemical Co., Ltd.), a cationic solution containing protamine (e.g., a commercially available product under the trade name of Protamine Sulfate, derived from salmon, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), or a cationic solution containing two or three of these in combination may also be used. Gelatin is extracted by applying heat to collagen, the main component of connective tissues such as animal skin, bones, and tendons, and chemically, its main component is a linear polymer (protein) of amino acids. It is a mixture whose main component is the triple helix structure of collagen molecules that has been unwound by thermal denaturation. It gels at low temperatures. It is thought that the use of such a coating agent will strengthen the capsule coating. Agar is a freeze-dried product made by solidifying the mucus of red algae such as Agar-agar (Tengusa) and Gracilaria verum (Gracilaria). Agar gels at a concentration of less than 1%, which is lower than that of gelatin. It gels at low temperatures. Once agar gel has solidified, it will not melt until it reaches 85°C or higher, so it is resistant to temperature changes and does not melt easily in the mouth. Agar's solidifying action comes from polysaccharides, so its solidification is not inhibited by the proteases contained in fruits such as pineapple and kiwi fruit. It can also be used when animal products are to be avoided. It is thought that the use of such coating agents strengthens the capsule coating.

[0050] Examples of coating agents that can be used include pectin and sodium alginate. Pectin is a complex polysaccharide contained in the cell walls and middle leaves of plants, and its main component is polygalacturonic acid, which is an α-1,4-bonded unit of galacturonic acid. Its molecular weight is 50,000 to 360,000, and it is found especially in the leaves, stems, and fruits of plants. It gels when an appropriate amount of sugar and acid are mixed and heated (hydrogen bond type gel). It also gels from low methoxyl pectin or pectic acid by calcium or other polyvalent metal ions (ion bond type gel). Sodium alginate also gels with calcium.

[0051] In this experimental example, a solution containing agar was used, but a solution containing gelatin (collagen) (for example, a commercially available product under the trade name Cook Gelatin, manufactured by Morinaga & Co., Ltd.) may be used, or a solution containing two types of agar and gelatin may be used. At least one selected from gelatin, agar, pectin, and sodium alginate may be used as a coating agent. In this experimental example, a cationic solution treatment was performed, and then a coating agent-containing solution treatment was performed, but any one of the treatments may be performed. The order may also be reversed. It is preferable to perform the cationic solution treatment first. The above-mentioned coating treatment did not cause a significant change in the thickness of the capsule coating, but the properties of the coating changed. For example, the substance added by the coating treatment may have functioned to suppress the plastic deformation of the original capsule coating.

[0052] [Capsule strength measurement] (Sample preparation) As described in Experimental Example 16, about 7 ml of the contents including the core material and the hardener were poured into a 3 cmφ hemispherical mold (Silicomart, Silicone Flex Hemisphere 30 mm), frozen in a freezer, and immersed in a 0.5% sodium alginate aqueous solution heated to 70°C as described above to form a capsule containing the contents. The formed sample was close to a hemispherical shape, but the relatively flat surface also swelled slightly, so there was a tendency to become spherical. Furthermore, when the height was measured with this surface as the bottom, it was within the range of 1.5 to 2.0 cm. The formed capsule containing the contents was flexible and elastic. This shape was selected so that the thickness and size of the food when eaten would be preferable, since the deformation area at the time of breaking is closely related to the actual masticatory movement. Each sample weighed about 7 g, and had a so-called kagami mochi shape, which was a circle of 3 cmφ when viewed from above and an ellipse when viewed from the side.

[0053] (Compression test) A creep meter (RE2-33005C, manufactured by Yamaden Co., Ltd.) was used for the compression test. A disk-shaped plunger (4 cmφ) sufficiently larger than the capsule diameter was used to approach the sample placed on the base surface from above at a load cell of 20 N and a speed of 1 mm / sec. The height at which the plunger came into contact with the sample during compression and began to sense pressure was defined as the sample height. The plunger was allowed to descend until it reached 20% of the sample height (up to a height compression rate of 80%). All of the tested samples were destroyed before reaching this compression rate. The load and displacement during this compression test were measured and analyzed using breaking strength analysis software. A compression test was performed on five samples for each type, and the arithmetic average values ​​of the breaking load and strain rate were calculated. The breaking load at this time can be called the breaking strength.

[0054] Figure 20 illustrates an example of capsule strength analysis. The vertical axis is the load (N), and the horizontal axis is the strain rate (%) based on the height. In this figure, the load increases almost linearly until the strain rate approaches 40%, and after reaching a maximum value at about 40%, the load suddenly decreases. This point was taken as the breaking point, and the prominent point was taken as the breaking load, which was interpreted as the hardness of the capsule. Since the breaking measurement corresponds to the chewing action, the setting of the compression speed was determined by a preliminary experiment. Here, the strain rate is a characteristic felt as the elasticity of the capsule, and the breaking load is considered to be a characteristic felt as the ease of breaking (chewing resistance). As a preliminary test, a sensitivity test was conducted to investigate the relationship between these characteristics from five subjects. Several samples were prepared in which the strain rate until breaking was about 30% to about 60%, and the subjects evaluated the elasticity. At this time, the samples were prepared under basically the same conditions as in Experimental Example 1, and the concentration, temperature, and immersion time of the sodium alginate aqueous solution were adjusted to adjust the film thickness so that the distortion rate was different. Although samples with a distortion rate of more than about 50 were ultimately destroyed, the majority reported a soft feeling. On the other hand, for samples with a distortion rate of 43% to 45%, the majority reported moderate elasticity and a pleasant bursting feeling. On the other hand, samples with extremely thin coatings burst just by pinching them. Furthermore, samples that had been coated as shown in Figure 3 were also sensorily evaluated. For coated samples with almost the same distortion rate (43% to 48%) as those without coating, the majority reported a more crisp feeling. From these findings, it is considered that a distortion rate of about 30% or more, about 35% or more, or about 40 is excellent in terms of texture. It is also considered that a distortion rate of about 80% or less, about 70% or less, or about 60% or less is excellent in terms of texture. Even if they were equivalent to the same distortion rate, the coated ones seemed to have a better texture. From the experiment, it was found that a distortion rate of about 30% corresponds to a range of about 4.5mm to about 5.7mm, a distortion rate of about 40% corresponds to a range of about 6.0mm to about 7.6mm, and a distortion rate of about 50% corresponds to a range of about 7.5mm to about 9.0mm.

[0055] FIG. 21 compares the breaking load and sample height of samples that have been coated as described above with those that have not been coated. The height of the samples was within the range of about 14 to 15 mm on the first day after production, and no difference was observed due to the presence or absence or amount of xanthan gum or the presence or absence of coating. However, on the fourth day after production, the uncoated samples maintained the same height, while the coated samples may have tended to become lower (e.g., concave). On the other hand, the breaking load is thought to tend to be higher for the coated samples. Also, even without coating, the breaking load tends to be higher when the amount of xanthan gum is large. As described above, a high breaking load tends to be associated with a high distortion rate, so a high breaking load may be perceived as being highly elastic.

[0056] (Experimental Example 17) A plurality of capsules of various types were prepared in the same manner as in Experimental Example 4, except that the amount of xanthan gum was 0%, 0.1%, and 0.25% by weight, and further, methylcellulose (MC) was 0.1% by weight. Furthermore, as shown in FIG. 3, a coating treatment was performed (S64). The capsules were immersed in a cationic solution treatment liquid and left to stand at room temperature for about 10 minutes. The cationic solution treatment liquid at this time contained 0.1% poly-L-lysine (product name: Salad Keep, manufactured by Okuno Chemical Industries Co., Ltd.). After that, the capsules that had been introduced for immersion were scooped up with a wire net and separated from the cationic solution treatment liquid.

[0057] Next, the capsules were immersed in a solution containing a coating agent and left to stand at room temperature for about 30 minutes. The solution containing the coating agent contained 0.5% (by weight) agar (agarose) (product name: powdered agar that dissolves in hot water, manufactured by Ina Food Industry Co., Ltd.). The capsules were then scooped up with a wire mesh, separated, and washed with deionized water.

[0058] FIG. 22 is a graph showing the effect of the presence or absence of methylcellulose on the breaking load of the sample on the first day after preparation. In this graph, 0% MC is the same as the breaking load on the first day in FIG. 21. FIG. 23 is a graph showing the effect of the presence or absence of methylcellulose on the height of the sample on the first day after preparation. In this graph, 0% MC is the same as the height of the sample on the first day in FIG. 21. FIG. 24 is a graph showing the effect of the presence or absence of methylcellulose on the breaking load of the sample on the fourth day after preparation. In this graph, 0% MC is the same as the breaking load on the fourth day in FIG. 21. FIG. 25 is a graph showing the effect of the presence or absence of methylcellulose on the height of the sample on the fourth day after preparation. In this graph, 0% MC is the same as the height of the sample on the fourth day in FIG. 21. From FIG. 22 and FIG. 24, it seems that even when methylcellulose is present, the breaking load tends to be larger when there is a coating treatment. On the other hand, from Figures 23 and 25, it appears that with methylcellulose, the height of the sample tends to remain constant (less likely to crumple) even four days after production, regardless of whether it was coated or not.

[0059] [Increasing the concentration of the core substance] As shown in Fig. 2, the food material produced in S24 in Fig. 1 can have a high concentration of core substance. For example, the capsule material obtained in the process in Fig. 1 is prepared (S42) and immersed in a high concentration of core substance (here, ethyl alcohol) for a predetermined time (S44). Since the coating is semi-permeable, the core substance penetrates into the capsule through the coating according to the concentration gradient. Next, the capsule food is removed from the solution (S46) and washed appropriately with deionized water or the like to obtain capsules containing a high concentration of core substance (S48).

[0060] (Experimental Example 18) Since the contents of the capsule are a mixture of a core substance and a hardener (with thickeners and the like added), the concentration of the core substance is reduced (approximately halved when mixed in equal amounts). Therefore, the capsule separated from the contact solution and washed was immersed in a solution with a high concentration of the core substance itself or the target of the core substance (e.g., ethyl alcohol in tequila), thereby improving the core substance concentration by utilizing the semipermeability of the coating. Specifically, the same capsule prepared in Experimental Example 1 was immersed for a predetermined time in a solution consisting of tequila concentrate, a tequila solution containing 2% calcium chloride, a 4% calcium lactate aqueous solution, and an equal amount of tequila concentrate (a solution in which the tequila concentrate is diluted twice (i.e., a solution with about 1 / 2 the ethyl alcohol content) or a solution in which a 4% calcium lactate aqueous solution is diluted twice with tequila (i.e., a 2% calcium lactate aqueous solution)), and the alcohol concentration of the contents was evaluated. A capsule was prepared that was left standing in the air as a control.

[0061] The results are shown in Figure 26. When immersed in tequila concentrate and tequila solution containing calcium chloride, the alcohol concentration peaked after 18 hours. It decreased thereafter, but there was almost no effect on the shelf life (after about 10 days). When stored without the liquid, the concentration gradually decreased, reaching almost half of what it was after 10 days.

[0062] (Experimental Example 19) As an additional experiment, an experiment was conducted in which equal amounts (volumes) of deionized water and 4% calcium lactate aqueous solution were mixed and used as the content, as in (Experimental Example 3). The solidification process was carried out by placing the capsules in a 3 cm hemispherical mold, a 5.8 cm spherical mold, and a 10 cm spherical mold. For contact with the contact solution, 0.5% (weight) and 1% (weight) sodium alginate aqueous solutions were used. Furthermore, some of the capsules were subsequently subjected to the highly elastic capsule treatment shown in Figure 3. Details are summarized in a table. [Table 1] In this way, capsules containing enormous amounts of content could be formed from small amounts.

[0063] As an option, as shown in FIG. 4, other characteristics can be imparted to the capsule material obtained in the process of FIG. 1. For example, it is possible to impart taste or flavor components. For example, the properties of the coating can be changed. Specifically, a smooth surface can be made rough. When the capsule material is placed in a liquid that produces ice crystals, such as water, and frozen, crystals are generated in the capsule membrane, and when thawed, unevenness is formed on the capsule surface. This unevenness reduces the slipperiness of the coating surface with other contacting solids, making it easier for the capsule to be held stably and more resistant to shaking during transportation. The processes of FIG. 2 to FIG. 4 may be performed alone, or two or more of them may be performed. For example, after producing the capsule material of FIG. 1, the alcohol concentration in the capsule contents of FIG. 2 is increased, and the method for producing a highly elastic capsule of FIG. 3 is performed, thereby producing a capsule with multiple characteristics.

[0064] In the experimental examples described so far, the core material and the hardener, etc., have been described as being mixed in equal amounts, but it is clear that this ratio can be freely changed. For example, the core material (e.g., as a solution) and the hardener, etc. (e.g., as a solution) can have any ratio from 1:99 to 99:1. Exemplary ratios include 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, or 90:10. [Explanation of symbols]

[0065] S12 Core substance production process S14 Hardener production process S16 Characteristic material production process S18 Dissolution, dispersion, mixing process S20 Contents production process S22 Contents solidification process S24 Contact process with contact liquid S26 Separation process from contact liquid S28 Capsule material production process S44 High alcohol concentration solution immersion process S65 Solution treatment process for coating materials S84 Processing of characteristic imparting solution 100 hemispherical 120 Star Shape 130 Heart-shaped mold 500 droplets 510 Solid substrate 520 Nozzle 522 Droplet

Claims

1. solidifying the content, including the core material and the hardener, to produce a solidified content; contacting the solidified contents with a contacting solution containing a film-forming agent; Separating the contacted coated contents from the contacting solution; and modifying the coated content; A method for producing a capsule, comprising:

2. The method of claim 1, wherein the improving step includes increasing the concentration of a core material in the content.

3. The method of claim 1 or 2, wherein the modifying step comprises modifying a coating.

4. 3. The method of claim 1, wherein the modifying step includes the step of introducing a dye into the content.

5. The method according to claim 1 or 2, wherein the improving step includes the step of introducing a water-soluble cellulose derivative into the content.

6. 3. The method of claim 1 or 2, wherein the modifying step includes the step of introducing a thickening agent into the content.

7. 3. The method according to claim 1, further comprising a step of heating the contact solution to 40° C. or higher in the contacting step.

8. 3. The method of claim 1, wherein the modifying step includes the step of introducing solids into the content.

9. The manufacturing method according to claim 1 or 2, wherein the improving step includes a step of solidifying the solidified content into a desired shape in the step of generating the solidified content.

10. A content including a core substance, the content being liquid at 0°C or higher; A coating that contains at least one gelatinous material selected from the group consisting of agar, carrageenan, gelatin, sodium alginate, calcium lactate, and pectin, and that contains the contents; The coating has an average thickness of 0.34 μm to 2 mm; the content is contained in a substantially spherically inflated container formed by the coating, is allowed to stand in the atmosphere, and is maintained in a liquid state; The capsule has a content of 6.3 ml or more.

11. 10. The capsule of claim 9, wherein the content contains 2% or more ethyl alcohol.

12. 11. The capsule according to claim 9, wherein the coating is a semipermeable membrane that is permeable to molecules having an average molecular weight of 1,000 or less.

13. 11. The capsule according to claim 9 or 10, wherein the content comprises fruit juice.

14. The capsule according to claim 9 or 10, characterized in that the filling material comprises a water-soluble cellulose derivative.

15. The capsule according to claim 9 or 10, characterized in that the filling contains a thickening agent.

16. 11. The capsule according to claim 9 or 10, wherein the coating seamlessly encases the contents.

17. 11. The capsule according to claim 9 or 10, wherein the content comprises a solid.

Citation Information

Patent Citations

  • Sesame flavor for acidic seasoning, and acidic seasoning containing the sesame flavor

    JP2007014252A

  • Soft capsule for preventing texture of food product from being deteriorated, and food product containing the soft capsule for preventing texture from being deteriorated and edible oil

    JP2018143101A

  • Soy sauce processed product and processed product of water-based liquid food and prepared food thereof and production method thereof

    JP2022114451A

  • Method for the encapsulation of a food product, and food product

    WO2011138478A1

Cited By

  • Double-layer soft glue film, preparation method and application thereof, and large-capacity capsule

    CN121466026A

  • Double-layer soft gelatin capsule and its preparation method and application to large-volume capsules

    CN121466026B